Quaker brotherhood : interracial activism and the American Friends Service Committee, 1917-1950 - Austin, Allan W. (University of Illinois Press, 2012)
'Quaker Brotherhood' is an extensive study of the American Friends Service Committee's interracial activism in the first half of the 20th century, filling a major gap in scholarship on the Quakers' race relations work from the AFSC's founding in 1917 to the beginnings of the civil rights movement in the early 1950s.